Mengurai Titik Temu Antara Istihsan dan Pembaharuan Hukum Islam - Farid Naya (IAIN Ambon, 2017)
Istihsan and renewal of Islamic law are two terms which on one side has a different meaning, but on the other hand, both have mutually corresponding relationships between each other tightly. Conceptually, istihsan means the shift of mujtahid in determining the law on an issue of which is comparable to that for their special proposition in the Qur’an or Sunnah. Istihsan is a method that emphasizes the maintenance of law istinbat maqasid al-shariah, namely the realization of human welfare. Mujtahid’s turning away from a law on an issue to which other law for the proposition that a more powerful is simply to maintain maqasid al-shariah. The Renewal of Islamic law, meaning the effort and act through a specific process with the utmost seriousness by those who have the competence and authority in the development of Islamic law (mujtahid) in ways that have been determined based on the rules istinbat law that allowed making Islamic law can appear more fresh and modern, not outdated. In addition, reform of Islamic law is to maintain law purposes (maqasid al-shariah) to produce legal provisions that address the issues and new developments brought about by the progress of science and modern technology. Thus, between istihsan and reform of Islamic law boils down to one point, namely the maintenance of Islamic shari’ah purposes (maqasid al-shariah). Keywords: istihsan, maqasid al-shariah, renewal of islamic law